Peningkatan Pemahaman dan Kepedulian Ibu Hamil Trimester III Terhadap Persiapan IMD dan Asi Eksklusif - Seventina Nurul Hidayah; Meyliya Qudriani; Juhrotun Nisa; Nora Rahmanindar; Evi Zulfiana; Nilatul Izah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Early Initiation of Breastfeeding (IMD) can prevent prelactal feeding and facilitate the breastfeeding process in the future, especially when exclusive breastfeeding is wanted. The aim of this community service is to directly increase the knowledge of third trimester pregnant women about IMD and exclusive breastfeeding. With this knowledge transfer process, it is hoped that there will be a change in behavior in preparation for breastfeeding. The implementation of the service uses more than one method. On the first occasion, an extension method was carried out with lectures and questions and answers. The second method is used to assess whether the extension material has been understood by the participants, namely a question and answer session. The implementation of community service, namely increasing understanding and awareness of third trimester pregnant women in Jenggawur Village, Pangkah District has been successful well executed. Participants were very enthusiastic in participating in these activities. This can seen from their active participation in asking questions when the resource person delivers theory. Of the 10 questions given, participants managed to answer 8 questions correctly. This service activity is necessary it is followed up with mentoring, because if it is only given counseling, it is feared that it will not be able to implement it properly.